The Role of Artificial Intelligence in Enhancing Library Services in Universities: A Bibliometric Analysis - Ankamah, Samuel; Vidza, Prince Yaw; Addo, Benjamin Nana (Ghana Library Journal, 2024)
The rapid evolution of Artificial Intelligence (AI) technologies presents a transformative opportunity for libraryservices, particularly within African universities. This study employed a comprehensive bibliometric analysis to map the trends and patterns and the impact of AI in enhancing library services in African universities. A total of616 datasets from Scopus (Elsevier), spanning from inception to 2023, were extracted, analysed, and visualisedusing tools like MS Excel, Harzing’s Publish or Perish, and VOSviewer. An information specialist crafted the requisite keywords and verified the final search strategy. The results indicate an increasing trend in publicationsfocused on AI’s role in enhancing library services within African universities. China, the United States, India, andNigeria are the most influential countries in this research domain, contributing 162 (23.41%), 132 (19.08%),32 (4.62%), and 26 (3.76%) publications, respectively. Wuhan University of Technology emerged as the mostinfluential institution, with seven (2%) publications. Citation analysis highlighted S. Gupta and S.K. Gupta (2019) and A.M. Cox et al. (2019) as the most cited articles in this field, with 147 and 130 citations, respectively. Keywords analysis revealed that “university libraries”, “libraries”, “data mining”, and “artificial intelligence” were the most frequently used author keywords, appearing in 171 (7.63%), 168 (7.49%), 120 (5.35%), and 117 (5.22%) publications, respectively. Co-occurrence analysis identified six clusters of interconnected concepts, thematically organised around libraries, data mining, academic libraries, artificial intelligence, deep learning, and machine learning. The results reveal a growing interest in AI-driven solutions for cataloguing, digital resource management, user interaction, and predictive analytics, highlighting both the benefits and challenges faced by African university libraries. The study concludes with practical recommendations for policymakers and library managers to optimise AI adoption and suggests avenues for future research to further enhance library services on the continent.